2008
DOI: 10.1038/emboj.2008.105
|View full text |Cite
|
Sign up to set email alerts
|

Activated macrophages promote Wnt signalling through tumour necrosis factor-α in gastric tumour cells

Abstract: The activation of Wnt/β-catenin signalling has an important function in gastrointestinal tumorigenesis. It has been suggested that the promotion of Wnt/β-catenin activity beyond the threshold is important for carcinogenesis. We herein investigated the role of macrophages in the promotion of Wnt/β-catenin activity in gastric tumorigenesis. We found β-catenin nuclear accumulation in macrophage-infiltrated dysplastic mucosa of the K19-Wnt1 mouse stomach. Moreover, macrophage depletion in ApcΔ716 mice resulted in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
218
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 263 publications
(228 citation statements)
references
References 33 publications
7
218
3
Order By: Relevance
“…Primers were purchased (Takara) and primer sequences are available upon request. Peter Vogt at the Scripps Research Institute, was transiently transfected as described 11 .…”
Section: Real-time Rt-pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…Primers were purchased (Takara) and primer sequences are available upon request. Peter Vogt at the Scripps Research Institute, was transiently transfected as described 11 .…”
Section: Real-time Rt-pcrmentioning
confidence: 99%
“…It has also been shown that β-catenin accumulation, a hallmark of Wnt activation, is particularly enhanced in the invasion front and metastasized colon cancer cells, suggesting that promotion of Wnt/β-catenin signaling is important for malignant progression 8 . Growth factors PDGF and HGF, as well as inflammatory cytokine TNF-α, have been shown to promote Wnt/β-catenin signaling activity in tumor cells [9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…TNF has a critical role in the pathogenesis of inflammatory bowel diseases (IBD) and is a therapeutic target for treatment of these disorders (54,67). Furthermore, mounting evidence suggests that TNF signaling is important in the pathogenesis of GI cancers (47,50,78). Specifically, an altered balance between prosurvival and apoptotic signaling stimulated by TNF may be critical for tumorigenesis (5,57).…”
mentioning
confidence: 99%
“…17 Another major player in this story with H.pylori infection is TNFa from infiltrating macrophages. 19 The TNFa promoted Wnt/b-catenin signaling in K19Wnt1 mouse stomach, and macrophage deletion in APC D716 mice suppressed intestinal tumorigenesis. Indeed, the importance of increased TNFa was clearly demonstrated in a colitis-associated colon cancer model where TNFR1 signaling in bone marrow-derived cells enhanced Wnt/b-catenin signaling in the epithelia, and TNFR1 knockout mice did not generate the same tumor number or load.…”
Section: R John Macleodmentioning
confidence: 99%
“…15 While the gastric cancer cell lines secrete Wnt5a to 4 The degradation complex composed of Auxin1 and adenomatous polyposis coli is linked to the Wnt/Fzd (frizzled)/LRP6 while b-catenin is released. 8 H.pylori can stimulate LRP6 phosphorylation, and TNFa from macrophages can increase Wnt/bcatenin signaling 19 in mouse stomach. Normal stomach turnover requires some Wnt/b-catenin signaling; 24,25 but how much is too much?…”
Section: R John Macleodmentioning
confidence: 99%